Sistema de transformação de solos hidromórficos-cambissolos na superfície de cimeira do Planalto do Espinhaço Meridional- Diamantina/MG - Roberta Borges Parreira (2018)
This study has identified and investigated a pedological transformation system in the Corrego da Roda basin, in the Diamantina Plateau, MG. Employing description, analysis and interpretation of data observed in field work and laboratory analysis to understand the behaviour of soils under the current pedobioclimatic conditions, as well as the relationship between its organization and position in the slope. The studied area is located in the southeast of Diamantina municipality, specifically in a summit surface that composes the Southern Espinhaço Plateau, that is located in a landscape hollow. The methodology applied encompassed: 1)field work: study in topossequence, with deformed and undeformed samples of soils in four soil profiles and three trenches along with the morphological description of materials; 2)analysis of secondary data and cartography (remote sensing and geoprocessing); 3)laboratory analysis: granulometry, clay dispersed in water; particle density; determination of organic carbon content; determination of iron content, obtained through Dithionite Citrate Sodium Bicarbonate and Acid Ammonium Oxalate and micromorphology. The results have shown that the soil and soil horizon organisation along the slope are resulting from the pedological transformation systems operation: Organosols in the hidromorphic slope zone, Gleisols and Gleisol-Cambisols in the transition zone and Haplic-Cambisols in the well-drained zone (higher slope). From identifying this pedological transformation system it was possible to detect the relations of each alteration zone that indicated the existence of genetic sequences of pedomorphological development. Each identified zone in the slope depicted an evolutionary stage of the soil as well as of the slope. Thus it was possible to point that: 1)the high and medium slope soils are relics of the hidromorphic coverage; 2)this hidromorphic coverage shows imbalance with the current pedobioclimatic conditions and previously occupied a greater area; 3)Corrego da Roda tends to evolve upwards, that is the drainage axis tends to deepen, dissecting the plateau and consequently obliterating the hidromorphic environment that still exists currently; 4)the current soil distribution and the landscape in the Corrego da Roda basin come from the development of the pedological transformation system; 5)the relic unit of the remaining flat summit surface is not an isolated phenomena in the landscape, because there are other occurrences of similar pedogeomorphological conditions in other areas of the Meridional Espinhaco Ridge.